2 - Engineering our Own Futures: Lessons on Holistic Development from Muslim Women’s Civil Society Groups in Nigeria, Ghana and Tanzania - Wallace, Adryan (Africa Development, 2021)
Muslim women’s organizations in East and West Africa have cultivated successful strategies to mitigate the varied domestic economic and political outcomes produced by globalization. Although China and the other BRICS countries are providing multi-polar development models, their results may not differ significantly from their western counterparts if groups that are often left out of the decision-making processes are not included. There is an urgent need for social scientists to make the experiences of African women as designers of development the central point of theorizing in order to inform how we conceptualize economic and political participation and measure inequality. This paper will utilize case studies from local women’s non-governmental and community-based organizations in Kano, Nigeria, Tamale, Ghana and Dar es Salaam, Tanzania to help develop mechanisms for sustainable economic growth and substantive representation which, I argue, can help generate state institutions that are more responsive to the needs of their citizens. Mainstreaming gender as an analytical frame is essential because it interrogates privilege, illustrates how it is distributed among and between women and men and provides insights into partnerships that can be forged across genders. Furthermore, the institutional linkages of women’s organizations both within and across national contexts strengthens the ability of African countries to look internally and share their development best practices through sub-regional entities and the African Union. Finally, civil society needs to be redefined and contextualized using the perspectives of citizens at the grassroots level to produce holistic policy recommendations for all three tiers of governance (domestic, sub-regional and regional).